Qualitative psychology. 14 : A practical guide to research methods - Smith, Jonathan A. (London : SAGE Publications, 2015)
Undertaking qualitative research in psychology can seem like a daunting and complex process, especially when it comes to selecting the most appropriate approach for your project or assignment. This book, written and edited by a world-leading group of academics and researchers, offers an accessible, critical and practical way into qualitative research in psychology. Each chapter provides a detailed, step-by-step guide to using a qualitative research method - from conversation analysis or focus groups to interpretative phenomenological analysis or narrative psychology. Whatever approach you choose to take, this book will ensure you get it right from the start. New to this third edition: a chapter on thematic analysis, a section on how to choose and select the most appropriate method for your project.
Keywords: elektronické knihy; electronic books; Psychology